Male allyship contributing to women’s empowerment in Hidden Figures - Agung, I Gusti Ayu Mahatma; Beratha, Ni Luh Sutjiati (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This study examined male allyship in Hidden Figures, focusing on how male characters support women’s empowerment in a racially and gender-biased workplace. Using the theory of male allyship proposed by Burrell & Morin (2025), it aimed to identify the forms of allyship and analyze their impact on women’s professional advancement. Employing qualitative content analysis, this research analyzed scenes that depict men’s supportive actions towards women facing structural discrimination. The findings revealed that male allyship took various forms, including fostering social capital through mentorship and sponsorship, confronting anti-diversity, equity, and inclusion (D.E.I) pushback with confidence and facts, leveraging resources to support development opportunities, clarifying that D.E.I did not promote unqualified candidates, positioning D.E.I as a competitive advantage, being visible advocates for inclusion, and sharing narratives that highlight the tangible benefits of D.E.I. These forms of allyship empowered women by creating opportunities, removing systemic barriers, and positioning diversity, equity, and inclusion as essential to organizational success. The study concluded that allyship grounded in fairness, respect, and integrity demonstrated that supporting women’s empowerment did not diminish masculinity or leadership credibility but instead strengthened collective achievement and built gender-inclusive environments.